Antibacterial Activity of Rhinacanthus nasutus (L.) Kurz Extract Against Bacteria with Dermatologic Relevance - พาณิชย์กุล, ผู้ช่วยศาสตราจารย์ ดร.ทัศนีย์; บู๊ฮวด, ณัฐพร; บู๊ฮวด, ณัฐพร; จันตรี, กัลยาภรณ์; กุลชนะภควัต, ดร.ทิวัตถ์; ปทุมาสูตร, พิสุทธิ์; รุ่งเรือง, ฤทธิพันธ์; อ่อนวิมล, นาถลดา (Journal of Food Health and Bioenvironmental Science, 2017)
Rhinacanthus nasutus has been traditionally used for skin treatment. From previous reports, the extracts of this traditional plant possess antibacterial activity. This study entailed macerating Rhinacanthus nasutus leaves in methanol, analyzed compounds of this extract by thin layer chromatography (TLC) and testing the antibacterial activity of this extract by using disc diffusion and broth dilution techniques against four bacteria strains, including Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli and Pseudomonas aeruginosa. The results showed that umbelliferone and lupeol are two compounds in this extract. By disc diffusion technique, 50 and 500 mg/ml of methanolic Rhinacanthus nasutus extract could inhibit growth of S. aureus, S. epidermidis, and E. coli but did not inhibit growth of P. aeruginosa. By broth dilution technique, the results of antibacterial activity were reported as minimum bactericidal concentration (MBC) and minimum inhibitory concentration at 90 % (MIC90) and 50 % (MIC50). We found that MIC90 of Rhinacanthus nasutus extract were 9.5±0.12, 9.65±0.11 and 9.8±0.10 mg/ml, and MIC50 were 6.4±0.05, 6.5±0.06 and 6.8±0.04 mg/ml to S. aureus, S. epidermidis, and E. coli, respectively, and the MBC of extracts to these three bacteria was 25 mg/ml. This study showed that Rhinacanthus nasutus extracts could inhibit growth of skin bacteria. The extract will be used to develop skin cleansing products, leading to increased value of Rhinacanthus nasutus.